2017
DOI: 10.1073/pnas.1618732114
|View full text |Cite
|
Sign up to set email alerts
|

An Exportin-1–dependent microRNA biogenesis pathway during human cell quiescence

Abstract: The reversible state of proliferative arrest known as "cellular quiescence" plays an important role in tissue homeostasis and stem cell biology. By analyzing the expression of miRNAs and miRNAprocessing factors during quiescence in primary human fibroblasts, we identified a group of miRNAs that are induced during quiescence despite markedly reduced expression of Exportin-5, a protein required for canonical miRNA biogenesis. The biogenesis of these quiescence-induced miRNAs is independent of Exportin-5 and depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…The recovery of (TMG)-capped RNAs was measured by RT-PCR amplification of well-known hypermethylated RNAs such as small nuclear RNA (snRNA) U7 (Figure 2) or small nucleolar RNA (snoRNA) U3 (Martinez et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery of (TMG)-capped RNAs was measured by RT-PCR amplification of well-known hypermethylated RNAs such as small nuclear RNA (snRNA) U7 (Figure 2) or small nucleolar RNA (snoRNA) U3 (Martinez et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have shown the ability to pull-down (TMG)-cap RNAs, such as snRNAs and snoRNAs, with specific antibodies against (TMG)-cap RNAs (Luhrmann et al ., 1982). Our previous publications demonstrated for the first time the pull-down of (TMG)-cap pri-miRNAs in human cells (Martinez et al , 2017). Understanding which RNAs could be modified with a TMG-cap will provide new important insights into RNA biogenesis in normal or disease-related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies showed a requirement of XPO5 to transport pre-miRNAs from the nucleus to the cytoplasm [2][3][4] , providing the evidence that XPO5 is an essential component of miRNA biogenesis 7 . However, XPO5-independent pre-miRNA export pathway was also reported 8,9 . Notably, 7methylguanosine-capped pre-miRNAs whose biogenesis is independent of the DROSHA/DGCR8 microprocessor are exported via the PHAX-XPO1 pathway 9 .…”
mentioning
confidence: 99%
“…Incubation of increasing amount of XPO5 leads to increased processing efficiency of pri-mir-19a (lanes 3-6). Incubation of increasing amount of the XPO5 mutant also results in increased processing efficiency of pri-mir-19a (lanes[8][9][10][11]. b Preincubation of XPO5 and XPO5 mutant enhances the microprocessor cleavage of truncated pri-mir-19a v1.…”
mentioning
confidence: 99%
“…Small non-coding RNA (microRNA) maturation occurs in the cytosol and requires efficient nuclear export through the karyopherin family member exportin 5 (XPO5) (9). A limited set of studies have also shown that aside from XPO5, the export of few precursor miRNAs occurs through XPO1 as well (10). The mRNAs have a distinct export mechanism that occurs with the help of adaptor serine/arginine rich proteins that promote the recruitment of heterodimeric mRNA export receptor NXF1-NXT1 which facilitates exit through the nuclear pore (11).…”
mentioning
confidence: 99%